2018
DOI: 10.1002/bio.3515
|View full text |Cite
|
Sign up to set email alerts
|

Design of a phosphinate‐based bioluminescent probe for superoxide radical anion imaging in living cells

Abstract: Superoxide radical anion (O ˙ ) as an important member of reactive oxygen species (ROS) plays a vital role both in physiology and pathology. Herein we designed and synthesized a novel phosphinate-based bioluminescence probe for O ˙ detection in living cells, which exhibited good sensitivity for capturing O ˙ at the nanomole level and high selectivity against other ROS. The probe was further found to be of low toxicity for living cells and was then successfully employed for sensing endogenous O ˙ by using phorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…179,180 A further study confirming that polystyrene particles are able to induce ROS production was conducted by Liu et al In their study they showed that polystyrene particles 500 nm in size could stimulate ROS generation in human liver cells. 181 Aside from polystyrene, an in vitro study using unmodified polyethylene particles with sizes ranging from 0.3 to 10 μm showed unequivocally that the plastic particles stimulated mice-derived macrophages to produce significant levels of cytokines such as IL-6, IL-1β, and TNF-α. 182 Furthermore, several studies of human patients have shown that normal usage of implants such as total joint replacements made of polyethylene can lead to the production of wear debris.…”
Section: Impact Of Nanoplastics On Human Healthmentioning
confidence: 99%
“…179,180 A further study confirming that polystyrene particles are able to induce ROS production was conducted by Liu et al In their study they showed that polystyrene particles 500 nm in size could stimulate ROS generation in human liver cells. 181 Aside from polystyrene, an in vitro study using unmodified polyethylene particles with sizes ranging from 0.3 to 10 μm showed unequivocally that the plastic particles stimulated mice-derived macrophages to produce significant levels of cytokines such as IL-6, IL-1β, and TNF-α. 182 Furthermore, several studies of human patients have shown that normal usage of implants such as total joint replacements made of polyethylene can lead to the production of wear debris.…”
Section: Impact Of Nanoplastics On Human Healthmentioning
confidence: 99%
“…Cationic polystyrene nanoparticles were shown to induce reactive oxygen species (ROS) production and endoplasmic reticulum (ER) stress in mouse macrophages and lung epithelial cells via aggregation of misfolded protein, leading to autophagic cell death of RAW 264.7 mouse macrophages and BEAS-2B lung epithelial cells [127,128]. While, unmodified or functionalized polystyrene was shown to induce apoptosis in several human cell types, including primary human alveolar macrophages (MAC), primary human alveolar type 2 (AT2) epithelial cells, human monocytic leukemia cell line (THP-1), human immortalized alveolar epithelial type 1 cells (TT1), human colon carcinoma cells (Caco-2), and human lung cancer cells (Calu-3) [129][130][131][132]; and polystyrene nanoparticles were shown to regulate ROS via long non-coding RNAs (e.g., linc -61, linc-50, linc-9, and linc-2) in Caenorhabditis elegans [142].…”
Section: Oxidative Stress and Apoptosismentioning
confidence: 99%
“…[22][23][24][25][26][27] In the firefly luciferase-luciferin BL system, firefly luciferase catalyzes its highspecific substrate (D-luciferin or 6 0 -aminoluciferin) to emit visible light with the assistance of ATP, O 2 and Mg 2+ . [28,29] Excitation light is not needed in this process, to avoid the inherent disturbances from fluorescence (e.g. photobleaching and autofluorescence), therefore, target signals can be collected with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%